(untitled) - Ferguson, Susan J. (Mountain View, Calif., 2001)
Shifting the Center is an anthology that explores the issues and diversity of contemporary families by presenting a balanced coverage of racial and ethnic variation, and integrating a diversity of family arrangements and processes.
Keywords: Family,Marriage,Kinship,Gia đình; United States,United States,United States,Nước Mỹ